Mobile banking services quality and its impact on customer satisfaction of Indonesian Islamic banks - Bayu Arie Fianto; Charissa Kezia Rahmawati; Indri Supriani (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – This study investigates the influential factors of mobile banking service quality dimension (enjoyment, security, ease, design, and application system) of Indonesian Islamic banks toward customer satisfaction.Methodology – This study uses 100 respondents who are Islamic mobile banking users in Indonesia and applies the Partial Least Square for Structural Equation Modeling (PLS-SEM) approach.Findings – This study reveals that the enjoyment, security, design, and application system of Islamic mobile banks significantly impact customer satisfaction. This study suggests that Islamic banks should pay more attention to increasing their mobile banking application systems, which is the most crucial factor influencing customer satisfaction.Research limitations – This study is limited to the sample of five top Islamic banks’ customers in Indonesia with 100 respondents. Thus, the result of this study cannot be generalized to other countries.Practical implications – The findings offer valuable insights into Islamic banks about improving their mobile banking services’ quality to gain more satisfied customers, which benefited their financial and non-financial performances.Originality – This study specifically involved users of Islamic mobile banking from five Islamic banks, received the Top Brand Award in 2019. Therefore, this study provides significant guidelines for the rest of the Islamic banks in Indonesia to improve their customer satisfaction using mobile banking by referring to the Top 5 Brand Award.